The Emphasis Of Methaphorical Form On Cultural Park - Harisdani, D. D; Chandra, A (Talenta Publisher, 2019)
Chinese in Indonesia as one of the diverse ethnicity had a long story in Medan’s development. Even though Chinese has been in Indonesia for a long time, the history of Chinese culture is rarely known by the public. The need for a medium to support this is to preserve the culture and history of Chinese. The inadequate medium for documenting and preserving the cultural history threatens the culture gradually lost in the age so that it needs a museum to document Chinese culture. As one of the local and international tourist destination, it needed a cultural museum with an iconic architectural emphasis of metaphorical form. To achieve the research objectives, the glass box method was used as a research method. With the emphasis form on the museum, it could enriched tourism destination and adding insight of local or international citizen about Chinese culture in Medan.